2020
DOI: 10.1097/ncc.0000000000000851
|View full text |Cite
|
Sign up to set email alerts
|

Pain Management Experiences Among Hospitalized Postcraniotomy Brain Tumor Patients

Abstract: Background Brain tumors account for the majority of central nervous system tumors, and most are removed by craniotomies. Many postcraniotomy patients experience moderate or severe pain after surgery, but patient perspectives on their experiences with pain management in the hospital have not been well described. Objective The aim of this study was to describe how patients who have undergone a craniotomy for brain tumor removal experience pain management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…(2014) , Sweden Describe how patients perceive the use of the numeric rating scale in post-operative pain assessments Individuals undergoing general and orthopaedic surgery, N = 25, (12 males, 13 females) Semi-structured interviews on postoperative day 1 and 5 Thematic analysis Patients perceived Numeric Rating Scale facilitated communication with health care providers. Participation was linked to using the Numeric Rating Scale Foust- Winton et al. (2021) , USA Describe experience of pain management while hospitalized Individuals undergoing neurosurgery, N = 27, (11 males, 15 females) Qualitative, descriptive semi-structured interviews Thematic analysis Communication with staff critical to how patients were able to manage their pain Henningsen et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2014) , Sweden Describe how patients perceive the use of the numeric rating scale in post-operative pain assessments Individuals undergoing general and orthopaedic surgery, N = 25, (12 males, 13 females) Semi-structured interviews on postoperative day 1 and 5 Thematic analysis Patients perceived Numeric Rating Scale facilitated communication with health care providers. Participation was linked to using the Numeric Rating Scale Foust- Winton et al. (2021) , USA Describe experience of pain management while hospitalized Individuals undergoing neurosurgery, N = 27, (11 males, 15 females) Qualitative, descriptive semi-structured interviews Thematic analysis Communication with staff critical to how patients were able to manage their pain Henningsen et al.…”
Section: Resultsmentioning
confidence: 99%
“…Nurses have been recognized as the clinicians most frequently involved in pain assessment and management ( Eriksson et al., 2014 ; Kaptain et al., 2017a ; McTier et al., 2014 ). Many of the studies included in this review demonstrated that nurses had a unique ability to establish rapport through communication, even in challenging settings like post-operative care, where patient contact is infrequent and brief ( Foust Winton et al., 2021 ; Kaptain et al., 2017a ). A sense of rapport with nurses was linked to feelings of calm and control amongst patients and was noted to influence patients’ overall levels of satisfaction ( Angelini et al., 2018 ; Foust Winton et al., 2021 ; Kaptain et al., 2017b ; Schwenkglenks et al., 2014 ; Tawil et al., 2018 ; Vu et al., 2021 ; Zoëga et al., 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other recently conducted studies also did not find any significant differences in craniotomies in emergency and elective procedures. 19,20 Adding acetaminophen and NSAIDS as adjuncts to opioids increase patient satisfaction with pain management. 21,22,23 There are several limitations to our study, firstly it is a single center study, and we did not have enough number of patients or enough variables changing over time that may hint towards a significant change.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings related to the ways in which the participants dealt with their pain and how healthcare providers managed it have been described elsewhere. 22 To better understand how the participants experienced the quality of their pain, the interviewer used prompts such as "Tell me more about what the pain felt like to you" and "How would you describe your pain." Interviews were audio-recorded and transcribed by a professional transcriptionist.…”
Section: Data Collectionmentioning
confidence: 99%
“…Complete demographic data for the sample have been published previously. 22 In summary, participants were between the ages of 21 and 83 years. Most participants were women, and most were White.…”
Section: Demographic and Medical Datamentioning
confidence: 99%